A Quantitative Ex Post Facto Study on the Influence of Academic Supervision and Principal Motivation on Teacher Discipline - Yushartina Yushartina; Bukman Lian; Mahasir Mahasir (Yayasan Sembilan Pemuda Indonesia, 2027)
This article examines the influence of academic supervision and principal motivation on teachers’ work discipline at SMA Negeri 1 Semendawai Barat, Ogan Komering Ulu Timur, South Sumatra. The study was developed from a quantitative ex post facto thesis using saturated sampling involving all 41 teachers at the school. Data were collected through closed questionnaires supported by interview and documentation data. Academic supervision was measured through harmonious relationships, needs analysis, strategy and media development, and evaluation or revision. Principal motivation was measured through achievement, affiliation, and power needs, while teacher work discipline was measured through punctuality, facility use, responsibility, and obedience to school rules. The instruments were valid and reliable, with Cronbach’s Alpha values of 0.980 for academic supervision, 0.978 for principal motivation, and 0.969 for teacher work discipline. The results show that academic supervision has a significant effect on teachers work discipline, with a reported contribution of 26.2%. Principal motivation also has a significant effect, with a reported contribution of 36.9%. Simultaneously, academic supervision and principal motivation have a significant influence on teachers work discipline, with a reported F value of 14.903 and a simultaneous contribution of 29.6%. These findings indicate that teacher discipline improves when principals provide systematic academic guidance and maintain motivational leadership. The study recommends that principals develop supervision programs that are collegial, constructive, and integrated with continuous motivation strategies.